Sexual Quality of Life in Women with Breast Cancer - Lovorka Brajkovic; Petra Sladic; Vanja Kopilaš (Health Psychology Research)
For women with breast cancer, sexual quality of life is one of the most disrupted aspects of life often associated with long-term physical and emotional difficulties. The main goal of this paper is to systematically review the literature to determine the level of sexual quality of life in women with breast cancer considering the individual and combined impact of grade, progression of the disease, type of treatment, body image, degree of depression, and anxiety, self-esteem, and social partner support and to determine whether the perception of the body, level of self-esteem and the presence of depressive and anxiety symptoms differ regarding different types of treatment or the level of partners' social support. Using the PRISMA method, all found literature published in electronic databases PubMed, EBSCO, and Hrcak were reviewed and resulted in 10 relevant scientific and review papers.